Hubungan Teori Konsumsi Ekonomi Islam dengan Konsep Etika Konsumsi dalam Pemikiran Yusuf Al-Qardhawi - Audia, Famela; Addailami, Yusuf; Wigati, Sri; Zahrah, Reisa Medyna (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2024)
This journal writing focuses on the economic thoughts of Yusuf Qaradhawi regarding Islamic economic ethics. Islam has established ethics dan values in every scientific discipline, including Islamic economics. According to Yusuf al-Qardhawi, Islamic economics is an economy based on divinity. By using the laws of Islamic sharia. Economic activities such as production, distribution, consumption are always related to God dan aim at God. Economic Ethics really needs to be conveyed in the era of globalization which often ignores moral dan ethical values. Yusuf al-Qrdhawi, in his moderate view, shows that the economic ethics he speaks of is a form of economic knowledge that will always maintain economic sustainability. In Islamic Economics, it is hoped that it will be guided by ethical dan moral values, encouraging a sense of responsibility dan awareness of one's actions dan their impact on the material dan spiritual dimensions of life.